2009
DOI: 10.21273/hortsci.44.1.206
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychological Health Conditions of Older Adults Classified as Gardeners or Nongardeners

Abstract: Additional index words. CHAMPS questionnaire, SF-36, hand function, bone mineral density, human issues in horticulture Abstract. The objective of this study was to compare the physical and psychological health conditions and leisure-time activities, particularly physical activities (PAs), of older gardeners and nongardeners. Fifty-three older adults were recruited from the community of Manhattan, KS. Three groups were classified based on results from the Community Healthy Activities Model Program for Seniors q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 23 publications
3
54
0
1
Order By: Relevance
“…In our previous research, older gardeners had greater hand strength and pinch force than older nongardeners (Park et al, 2009). However, for older gardeners with arthritis, gripping tightly can cause pain and swelling of the knuckles.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our previous research, older gardeners had greater hand strength and pinch force than older nongardeners (Park et al, 2009). However, for older gardeners with arthritis, gripping tightly can cause pain and swelling of the knuckles.…”
Section: Discussionmentioning
confidence: 80%
“…In our previous research, gardening by older gardeners was determined to be moderate intensity physical activity and the older gardeners met the physical activity recommendation for health (at least 30 minutes of moderate intensity physical activity on most days of the week) through their daily gardening (Park, Shoemaker, & Haub, 2008). Older gardeners also reported better overall physical health and hand function abilities (hand strength and pinch force) than nongardening older adults (Park, Shoemaker, & Haub, 2009). Reynolds (1999) reported that grip strength improved after a 6-month gardening program and improvement in cardiovascular fitness was expected because gardening activities elevated the heart rate of participants.…”
Section: Abstract Physical Activity Bodily Pain Lower Back Pain Humentioning
confidence: 99%
“…For studies that measured health outcomes during gardening on multiple occasions, we used only data points at the start (control) and end (treatment). One study (Park et al, 2009) compared health outcomes of people with multiple levels of gardening activity (non-gardeners, gardeners, and active gardeners; here, active gardeners were defined as those who met or exceeded recommended physical activity levels by gardening, and gardeners as those who did not meet this recommendation by gardening but did garden as moderate intensity). In this case, we compared only non-gardeners and gardeners.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Park and others showed that gardening was an effective way for adults to meet the national guidelines for moderate to vigorous physical activity (Park, Shoemaker, & Haub, 2009). In other studies, urban gardeners reported fruit and vegetable intake levels that met national guidelines for fruit and vegetable consumption (Alaimo, Packnett, Miles, & Kruger, 2008; Litt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%